The art of resistance : cultural protest against the Austrian far right in the early twenty-first century - Fiddler, Allyson (Austrian and Habsburg studies ;, 2019)
"Well before the far-right resurgence that has most recently transformed European politics, Austria's 1999 parliamentary elections surprised the world with the unexpected success of the Freedom Party of Austria and its charismatic leader, Jörg Haider. The party's perceived xenophobia, isolationism, and unabashed nationalism in turn inspired a massive protest movement that expressed opposition not only through street protests but also in novels, plays, films, and music. Through careful readings of this varied cultural output, The Art of Resistance traces the aesthetic styles and strategies deployed during this time, providing critical context for understanding modern Austrian history as well as the European protest movements of today"--